Formulation development, characterization, and optimization of Eudragit–cinnamon essential oil-based nanoplatform and its efficacy against resistant bacteria - Touseef Nawaz; Niamat Ullah; Muhammad Ali; Safia Obaidur Rab; Safia Obaidur Rab; Irfan Ahmad; Irfan Ahmad; Rabia Baloch; Sadia Chaman; Kifayat Ullah Shah; Adnan Amin; Adnan Amin (Frontiers in Chemistry)
IntroductionMicrobial resistance is a growing global concern, necessitating the development of novel drug delivery system to combat the resistant bacterial strains. We aimed to formulate Eudragit based cinnamon essential oil loaded nanoplatform against resistant microbial strain.MethodsNanoparticles were characterized for zeta potential, PDI, particle size, SEM, FTIR, entrapment efficiency and drug release kinetic. Box Behnken design with the quadratic model was used to check the effect of independent factors and dependent factors.Results and DiscussionThe Klebsiella and Staphylococcus aureus have shown same MIC value of 1.25 μL/ml while E. coli and Pseudomonas aeruginosa shown 0.078 and 0.625 μL/ml respectively. Quadratic polynomial equation depicted that stirring speed exhibited negative effect on the PDI, particle size and encapsulation efficiency. The polymer concentration produced positive effect on the particle size, PDI and encapsulation efficiency of the nanoparticles. The predicted response values were as particle size (Y1) 228.9 nm, PDI (Y2) 0.3 and %EE (Y3) 72.75% which were very close to the actual values of response as particle size (Y1) was 230.4 ± 3.46 nm, PDI (Y2) was 0.293 ± 0.022, and %EE (Y3) was 74.9 ± 2.32%. It was concluded that our prepared formulation can be effectively used treat resistant bacterial infections.